Penerapan Aplikasi Canva pada Pembelajaran SBDP Kelas VI Semester I Materi Membuat Poster - Rizki Septa Hardhita (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: Technological developments require teachers to be able to develop their expertise, especially in the field of technology. Technological developments also make learning more interesting for students, especially when teachers want to explore information, especially learning media. Canva is a design program that is chosen by teachers to be used as learning media for students. Based on the results of the explanation above, it can be concluded that along with the development of the era, learning media is very necessary to support an education. The media currently being developed puts more emphasis on technology and communication to be implemented in schools, one of which is SBdP learning. Learning media such as teacher aids to teach material to students, so that students will be more interested and can also increase creativity and skills in learning at school. Abstrak: Perkembangan teknologi menuntut guru untuk dapat mengembangkan keahliannya, terutama dalam bidang teknologi. Perkembangan teknologi juga mengakibatkan pembelajaran menjadi lebih menarik bagi peserta didik, khususnya ketika guru ingin menggali informasi khususnya media pembelajaran. Canva merupakan program desain yang menjadi pilihan guru untuk dijadikan media pembelajaran bagi peserta didik. Berdasarkan hasil pemaparan di atas dapat disimpulkan bahwa seiring perkembangan jaman media pembelajaran sangat diperlukan untuk menunjang suatu pendidikan. Media yang dikembangkan saat ini lebih mengedepankan teknologi dan komunikasi untuk diimplementasikan di sekolah, salah satunya pembelajaran SBdP. Media pembelajaran seperti alat bantu guru untuk membelajarkan materi kepada peserta didik, sehingga peserta didik akan lebih tertarik dan juga dapat meningkatkan kreativitas dan keterampilan dalam pembelajaran di sekolah.